Ideological differences in COVID-19 vaccine intention: the effects of trust in the healthcare system, in complementary and alternative medicine, and perceived threat from the disease - Lamot, Monika; Kerman, Katja; Kirbiš, Andrej (Frontiers in Psychology, 2024)
Introduction Politically left-leaning individuals are more likely to get vaccinated against COVID-19, although little is known about the mechanisms underlying the ideological differences in vaccination intentions. Understanding the extent to which trust in the healthcare system, in complementary and alternative medicine, and the perceived threat from the disease contribute to these disparities is crucial, as it could inform targeted interventions to address vaccine hesitancy across the political spectrum. Methods The present cross-sectional study conducted among adults living in Slovenia (n = 858) examined the mediating role of trust in the healthcare system, trust in complementary and alternative medicine (CAM), and the perceived threat from the virus on COVID-19 vaccination intention. Results We found that leftist ideology and trust in the healthcare system positively predicted vaccination intention, whereas CAM negatively predicted this intention. In addition, left-leaning individuals expressed greater trust in the healthcare system and lower trust in CAM, resulting in higher levels of COVID-19 vaccination intention. The serial mediation model confirmed that trust in CAM was a negative predictor, while trust in the healthcare system positively predicted perceived threat. Discussion When dealing with vaccine hesitancy among right-oriented individuals, strategies should focus on enhancing trust in the healthcare system and critically evaluating the reliance on CAM.